Is There a Link Between Employer-Provided Health Insurance and Job Mobility? Evidence from Recent Micro Data - Benjamin W. Chute; Phanindra V. Wunnava (Institute for the Study of Labor (IZA), 2015)
This study investigates the prevalence and severity of job immobility induced by the provision of employer-sponsored health insurance a phenomenon known as 'job-lock'. Using data from the National Longitudinal Survey of Youth from 1994 to 2010, job-lock is identified by measuring the impact of employer-sponsored health insurance on voluntary job turnover frequency. Estimates from a logistic regression with random effects indicate that job-lock reduces voluntary job turnover by 20% per year. These results that are consistent with past research and are also supported by two alternative identification strategies employed in this paper. Our results indicate a persistence of the job-lock effect, despite two major policy interventions designed to mitigate it (COBRA and HIPAA) and signal a fundamental misunderstanding of its causes. Both policies made health insurance more portable between employers, but this paper presents evidence from a quasi-natural experiment to suggest that the problem is a lack of viable alternative private sources of health insurance. In this model, we find evidence that access to health insurance through one's spouse or partner dramatically increases voluntary job turnover. This finding has significant bearing on predicted impacts of the Patient Protection and Affordable Care Act (2010) and the individual health insurance exchanges catalyzed by it; these new markets will create risk pools that may 'unlock' a job-locked individual by providing them a viable alternative to employer-sponsored health insurance.
Keywords: I13; J16; J32; J51; 330; job-lock; COBRA (1985); HIPAA (1996); Affordable Care Act (2010); random effects; difference-in-difference; voluntary job switch